Fun home : a family tragicomic - Bechdel, Alison, 1960- (Houghton Mifflin, 2006)
This book takes its place alongside the unnerving, memorable, darkly funny family memoirs of Augusten Burroughs and Mary Karr. It's a father-daughter tale perfectly suited to the graphic memoir form. Meet Alison's father, a historic preservation expert and obsessive restorer of the family's Victorian house, a third-generation funeral home director, a high school English teacher, an icily distant parent, and a closeted homosexual who, as it turns out, is involved with male students and a family babysitter. Through narrative that is alternately heartbreaking and fiercely funny, we are drawn into a daughter's complex yearning for her father. And yet, apart from assigned stints dusting caskets at the family-owned 'fun home,' as Alison and her brothers call it, the relationship achieves its most intimate expression through the shared code of books. When Alison comes out as homosexual herself in late adolescence, the denouement is swift, graphic, and redemptive.--From publisher description.